1998
DOI: 10.1056/nejm199801153380301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computed Tomography of the Appendix on Treatment of Patients and Use of Hospital Resources

Abstract: Routine appendiceal CT performed in patients who present with suspected appendicitis improves patient care and reduces the use of hospital resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
253
1
26

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(284 citation statements)
references
References 19 publications
4
253
1
26
Order By: Relevance
“…High accuracy of CT has been reported for appendicitis and for acute diverticulitis (98%) [3,4]. A study evaluating the diagnostic value of abdominal CT in patients with acute abdominal pain in general also showed good results, with an accuracy of 78% for CT, including clinical evaluation [5].…”
Section: Introductionmentioning
confidence: 89%
“…High accuracy of CT has been reported for appendicitis and for acute diverticulitis (98%) [3,4]. A study evaluating the diagnostic value of abdominal CT in patients with acute abdominal pain in general also showed good results, with an accuracy of 78% for CT, including clinical evaluation [5].…”
Section: Introductionmentioning
confidence: 89%
“…The value of US in the diagnosis and management of appendicitis is well established world wide. In fact computed tomography is also being widely and increasingly used in the diagnosis and management of appendicitis [14]. However, keeping in view of ready availability, high accuracy in diagnosing appendicitis and much less expenses involved, US becomes the first modality of imaging investigation of choice in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that CT affects the treatment of appendicitis by avoidance of unnecessary appendectomy, avoidance of unnecessary observations, and exclusion of other pathologies [1,10,12,13]. By avoiding unnecessary operations, CT reduces the cost of treatment [14].…”
Section: Discussionmentioning
confidence: 99%